Studi Transformasi Morfologi Tata Guna Lahan Koridor Braga - Tabitha Hemastuti; Weishaguna (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. The Braga Corridor experienced physical development from the center of Bandung which resulted in the problem of physical space unity. One of its phenomena is characterized by the presence of dead buildings and conditions of trade and services that have disappeared from their historical existence. From this phenomenon, an issue was obtained, namely the occurrence of problems of physical space unity, especially the morphology of land use in the Braga corridor. Based on the issue, the study question arises, namely "How is the transformation that occurred in the morphology of land use in the Braga corridor?" So that the purpose of this study is to identify transformations that occur in the morphology of land use in the Braga corridor. Epistemologically, the study uses the morphological theory of cities. Axiologically, this study uses a morphological approach with synchronous and diachronic analysis methods by comparing maps of historical periods with existing maps. The conclusion of this study is that the transformations that occurred in the morphology of the Braga corridor were quite high and resulted in their identity or historical relics being lost slowly due to increasingly uncontrollable developments. Abstrak. Koridor Braga mengalami perkembangan fisik dari pusat Kota Bandung yang mengakibatkan terjadinya masalah kesatuan ruang fisik. Salah satu fenomenanya ditandai dengan adanya bangunan mati dan kondisi perdagangan dan jasa yang sudah hilang dari eksistensi sejarahnya. Dari fenomena tersebut didapatkan isu yaitu terjadinya permasalahan kesatuan ruang fisik terutama morfologi tata guna lahan pada koridor Braga. Berdasarkan isu, muncul pertanyaan studi yaitu “Bagaimana transformasi yang terjadi pada morfologi tata guna lahan di koridor Braga?” Sehingga tujuan dari penelitian ini yaitu mengidentifikasi transformasi yang terjadi pada morfologi tata guna lahan di koridor Braga. Secara epistimologi, studi ini menggunakan teori morfologi kota. Secara aksiologi, studi ini menggunakan pendekatan morfologi dengan metode analisis sinkronik dan diakronik dengan cara membandingkan peta-peta periode sejarah dengan peta eksisting. Kesimpulan dari studi ini yaitu teridentifikasi transformasi yang terjadi pada morfologi koridor Braga cukup tinggi dan mengakibatkan identitas atau peninggalan sejarahnya hilang perlahan karena perkembangan yang semakin tidak terkendali.